Intestinal Helminthes Parasite among Public and Private School Children of Nepal - Subedi, Janak Raj; Gaire, Krishna Prasad; Devkota, Ravi Prasad (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Gastrointestinal infections impose a great and often silent burden of morbidity and mortality on poor populations in developing countries. School age children are one of the groups at high-risk for intestinal parasitic infections. The objective of this study was to compare the prevalence rate of intestinal helminthes parasites among private and public school children of Devdaha Municipality of Rupandehi district and to determine the association of prevalence with different risk factors. Material and methods: The study was carried out during June to July 2019. A total of 150 (75 from public and 75 from private school) stool samples were collected in clean, dry and screw capped plastic vials and were studied for the presence of intestinal helminthes parasites using direct smear method. Results: Overall parasitic prevalence rate was 18.66% (28/150). Prevalence rate was considerably higher in public school children (22.66%; 17/75) compared with private school (14.66%; 11/75) (P>0.05). The prevalence of helminthes parasitic infections was statistically independent with age and gender of the students (P>0.05). The current finding was maximum for single parasitic infection in both public (88.23%) and private (90.90%) school. Total four genera of parasites were identified. Among them, Ascaris lumbricoides was most common followed by Trichuris trichiura, Hookworms and Taenia sp. Conclusion: Transmissions of infections were generally due to poor sanitary habits, use of contaminated drinking water and improper disposal management. This study suggests the need of health education program in schools along with regular screening of intestinal parasites and periodic administration of anti-parasitic drugs for the effective management of the intestinal parasitic infections among school children in Nepal.